Effect of raw grain feeding on obesity factors: Raw Grain Feeding - Park, Jong Suk; Hwang, Tae Hyun; Son, Yeon Hee (Progress in Nutrition, 2021)
Obesity is known to cause metabolic disorders such as hyperlipidemia and hypertension, among other diseases, and contribute to mental illnesses such as depressive disorder. The westernization of the Korean diet has led to an increase in the prevalence of obesity in Korea. Diet therapy is considered to have the easiest and quickest effect in obesity treatment of all the modalities; however, it is associated with nutritional imbalances due to calorie restriction. This study aimed to ascertain whether the intake of raw grains as food substitutes can effectively treat obesity. A total of 30 participants underwent diet therapy for obesity treatment, with some meals replaced by raw grains rich in nutrition. In the control group, the body weight decreased to 99.51±2.62% while in the experiment group, it decreased to 95.33±3.74% (p<0.001). In the control group, the skeletal muscle weight increased to 98.94±8.39% while in the experiment group, it increased to 87.03±13.02% (p<0.01). In terms of fat mass, the value in the control group increased to 103.3±1.23% while that in the experiment group decreased to 95.2±51.37% (p<0.05). In terms of extracellular water ratio, the value in the control group decreased to 99.75±3.14% while that in the experiment group decreased to 97.34±4.02% (p<0.05). The body mass index (BMI) in the control group decreased to 100.04±5.78% while that in the experiment group decreased to 95.23±8.53% (p<0.05). Individual participant research was conducted to complement the weakness of the population sample number; in this, weight and BMI values were found to decrease under conditions of imbalanced nutrition. It was ascertained that participants’ dietary habits were corrected through control even when raw grain intake was discontinued.